Experimental evaluation of drying of banana using a double-pass solar collector (DPSC) and theoretical analysis using a CFD model. Issue 1 (1st January 2020) - Mutabilwa, Philemon X.; Nwaigwe, Kevin N.
Abstract: Preservation of banana through drying is a recommended method for improving the shelf life. In this study, an experimental and theoretical evaluation of a developed forced-convection indirect solar drying system with a double-pass solar collector (DPSC) was undertaken. Experimentation using banana slices of 4 mm thickness was carried out. The DPSC achieved an optimal peak outlet temperature of 72°C with a maximum operational efficiency of 72.5%. A computational fluid dynamic (CFD) model was developed for prediction of the dryer temperature and 3D airflow distribution within the dryer unit using ANSYS 18.2. The CFD model was validated using experimental data and good agreement was achieved. The developed dryer demonstrated improved efficiency over similar dryers, and this is attributable to the unique arrangement of component parts. Dried banana chips were evaluated for quality through taste, color and shape and the results indicated good quality products. This was attributed to the pretreatment of banana chips with lemon juice prior to drying.